Investor Awareness and Investment on Equity in Nepalese Capital Market - Kadariya, Sudarshan; Subedi, Phul Prasad; Joshi, Bharati; Nyaupane, Ram Prasad (Banking Journal, 2012)
Keywords: Access; Awareness; Information; Investment; Stock Market DOI: http://dx.doi.org/10.3126/bj.v2i1.5702 Banking Journal 2012; 2(1): 1-15